A Review of participant, agency, and community outcomes of non-familial intergenerational programs. (January 2023) - Steward, Andrew; Hasche, Leslie; Greenfield, Jennifer C.; Ingle, M. Pilar; De Fries, Carson; Fix, Rachel; King McLaughlin, Jessica; Schilz, Matthew; Hennig, Michaela; Bonatus, Devyn
Summary: Social workers are uniquely qualified to administer intergenerational programs, which offer a long-standing and promising way to improve the lives of children, youth, older adults, and communities. Existing reviews of intergenerational programming include a relatively limited time period and do not include agency and community outcomes. This scoping review was conducted with two primary objectives: (1) to synthesize a more comprehensive understanding of intergenerational program outcomes, organized by program type, and (2) to clarify gaps related to agency and community-level outcomes. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review (PRISMA-ScR) guidelines, we searched 18 databases for articles published between 1981 − 2019. Quantitative, qualitative, and gray literature were included that focused on formal, non-familial intergenerational programs and incorporated clear research methods. A two-cycle coding process identified six program types, five participant outcome domains, three agency-level outcomes, and four community-level outcomes. Findings: 217 articles met inclusion criteria after a first (title/abstract) and second (full-text) review. Quality appraisal of the articles found the studies to have "fair" quality overall, with a limited number of randomized controlled trials or sustained outcomes greater than six months. Approximately 12% of studies identified agency or community outcomes. Findings indicate strong psycho-social outcomes for older adults and increased inclusivity, capacity, and engagement at agency and community levels. Applications: Future program development and research efforts should address best practices for the implementation and scalability of intergenerational programs to enhance capacity and age-inclusivity at agency and community levels.